MONITORING CCTV DIGITAL SECARA ONLINE MELALUI INTERNET & MOBILE PHONE PADA JARINGAN WIRELESS LAN: STUDI KASUS PADAPT TIGA SINAR MANDIRI (CKI ON SPOT, 2016)
One of the newest ways that we can directly monitor the event or to monitor the condition of the company's assets and the personal wealth is with the installation of CCTV Digital. Digital CCTV can be monitored with the Internet browser from any location in the world as long as there is Internet connection both in home and mobile Internet such as blackberry, androit and others. For all purposes will be success even it should be done setting Wireless LAN and Network Address Translation settings correctly on the Digital Video Recorder and Wifi Router is used. When everything is installed properly then the asset security and computer network security will be utilized and safe from hacker attacks..